Cytotoxicity of Donor Natural Killer Cells to Allo-Reactive T Cells Are Related With Acute Graft-vs.-Host-Disease Following Allogeneic Stem Cell Transplantation - Sheng, Lixia; Mu, Qitian; Wu, Xiaoqing; Yang, Shujun; Zhu, Huiling; Wang, Jiaping; Lai, Yanli; Wu, Hao; Sun, Ye; Hu, Yongxian; Fu, Huarui; Wang, Yi; et al. (Frontiers in Immunology, 2020)
Objectives: The mechanism and immunoregulatory role of natural killer (NK) cells in human graft-versus-host-disease (GVHD) remains unclear. This study quantitatively analyzed the cytotoxicity of donor NK cells towards alloreactive T cells, and investigated their relationship with acute GVHD (aGVHD). Methods: We evaluated NK dose, subgroup, receptor expression in allografts from 98 patients receiving allogeneic hematopoietic stem cell transplantation (allo-HSCT). A CD107a degranulating assay was used as a quantitative detection method for the cytotoxic function of donor NK cells to alloreactive T cells. In blocking experiments, NK cells were pre-treated with anti-NKG2D, anti-CD226, anti-NKP46 or anti-NKG-2A monoclonal antibodies (mAbs). Results: NK cells in allografts effectively inhibited auto-T cell proliferation following alloantigen stimulation, selectively killing alloantigen activated T cells. NKG2A- NK cell subgroups showed higher levels of CD107a degranulation to activated T cells, when compared with NKG2A- subgroups. Blocking NKG2D or CD226 (DNAM-1) led to signiﬁcant reductions in degranulation, whereas NKG2A block resulted in increased NK degranulation. Donor NK cells in the aGVHD group, expressed lower levels of NKG2D and CD226, higher levels of NKG2A, and showed higher CD107a degranulation levels when compared with NK cells in the non-aGVHD group. Using univariate analysis, higher NK degranulation activities in allografts (CD107ahigh) were correlated with a decreased risk in grades I–IV aGVHD (hazard risk (HR) = 0.294; P < 0.0001), grades III–IV aGVHD (HR = 0.102; P < 0.0001) and relapse (HR = 0.157; P = 0.015), and improved overall survival (HR = 0.355; P = 0.028) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Multivariate analyses showed that higher NK degranulation activities (CD107ahigh) in allografts were independent risk factors for grades, I–IV aGVHD (HR = 0.357; P = 0.002), and grades III–IV aGVHD (HR = 0.13; P = 0.009). Conclusions: These findings reveal that the degranulation activity of NK in allografts towards allo-activated T cells was associated with the occurrence and the severity of aGVHD, after allogeneic stem cell transplantation. This suggested that cytotoxicity of donor NK cells to alloreactive T cells have important role in GVHD regulation.